ANALYSIS THE BEHAVIOR OF INVESTOR IN CONDUCTING CRYPTOCURRENCY INVESTMENT ACTIVITIES THROUGH THE CREDIBILITY OF CELEBRITIES - Ina Agustini Murwani; Jessi Julianti; Nauval Mahdi; M. Rafli Rulianto Putra (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The objective of this study is to see the influence of the credibility of celebrity endorsers behind the intentions and behavior of consumers towards crypto investment. This study uses a questionnaire as a data collection tool, therefore the research is quantitative. This research design uses a descriptive design by setting a clear data collection plan. The data analysis technique uses statistical methods and in carrying out data calculations using Partial Least Square (PLS). The study reveals that while the Attitude Towards Adopt Crypto does not significantly influence the Intention to invest, celebrity endorsements (Attractiveness, Expertise, and Trustworthiness) play a crucial role in shaping attitudes, perceived behavioral control, and subjective norms related to cryptocurrency adoption. These endorsements significantly impact the Intention to invest, which in turn affects actual investment Behavior. The strong influence of subjective norms on intention highlights the importance of social pressure and the opinions of celebrities in motivating individuals to invest in cryptocurrencies. Consequently, leveraging celebrities' attractiveness, trustworthiness, and expertise can effectively drive cryptocurrency adoption among potential investors, especially within the productive age group of 25-35 years, predominantly housewives.